Anesthesia and enhanced recovery in subxiphoid video-assisted thoracoscopic surgery - Chen, Zhigang; Ali, Jason M.; Xu, Huan; Jiang, Lei; Aresu, Giuseppe (Journal of Thoracic Disease, 2018)
Subxiphoid video-assisted thoracoscopic surgery (VATS) is a surgical approach in minimally invasive thoracic surgery that aims to aid enhanced recovery by reducing postoperative pain by avoiding instrumentation of the intercostal spaces. Access through a subxiphoid port presents challenges for both the surgeon and anaesthetist. Particularly for left sided procedures, the heart can be compressed resulting in arrhythmia and haemodynamic compromise. The anaesthetic team play an important role in ensuring the success of subxiphoid VATS procedures. The key is continuous and comprehensive monitoring for circulatory disturbance and arrhythmia intraoperatively. Should arrhythmia develop it is important that it is managed rapidly and effectively in such a manner to minimize haemodynamic disturbance. In this article, important considerations for anaesthesia in subxiphoid VATS procedures is presented and solutions presented.